Requirements Engineering: Foundation for Software Quality 15th International Working Conference, REFSQ 2009 Amsterdam, The Netherlands, June 8-9, 2009 Proceedings - Glinz, Martin.; Heymans, Patrick. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 15th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2009, held in Amsterdam, The Netherlands, in June 2009. The 14 revised full papers were carefully reviewed and selected from 49 submissions. The papers are organized in thematic sections on value and risk, change and evolution, interactions and inconsistencies, organization and structuring, experience, elicitation, research methods, behavior modeling, empirical studies, and open-source RE.